Identidades de la madre privada de la libertad : Mujer, madre e infractora (2021)
Women deprived of liberty are a population with identities marked by vulnerability, to which the category of "offender" is added, which socially weakens their credibility as women and especially as mothers. Thus, it is intended to critically reflect on the construction of their identities as offenders, women, and mothers which are configured in the deprivation of liberty, based on the bibliographic review and personal constructions from a radical feminist perspective and with a focus on social identity. Discussing the categorizations they assumed before and during imprisonment, such as being women, mothers, low class, offenders, victims, and on many occasions, addicts, immersed in a patriarchal and capitalist system that judges, excludes and undermines them before and during the deprivation of their liberty, the influence of prisons in reinforcing the negative perception that women construct of themselves from punitive and patriarchal discourses and acts is also analyzed.